Magnetic circuit analysis to obtain the magnetic permeability of magnetorheological elastomers - Bastola, Anil Kumar (2020)
The magnetic permeability of magnetorheological elastomers must be known for their long-term use in the actual engineering systems. In this article, the magnetic permeability of both isotropic and anisotropic magnetorheological elastomers has been determined using a new method. The magnetic induction was measured and a closed magnetic circuit analysis was carried out to obtain the magnetic permeability of magnetorheological elastomers for both isotropic and anisotropic magnetorheological elastomers with 10%–50% volume concentration of carbonyl iron particles. The magnetic permeability was increased with increasing particle concentration for both isotropic and anisotropic magnetorheological elastomers as we could expect. The isotropic permeability is always lower than the anisotropic permeability. The maximum relative permeability value of 6.6 was obtained for 50% particle volume concentration. The experimental results also show a good agreement with theoretical predictions and previous investigations.